Sirens and sea monsters: tales from the odyssey - Osborne, Mary Pope; Homer (Tradewind Vancouver, B.C., 2005)
After returning from the Land of the Dead, Odysseus and his men are warned that the rest of his journey will remain challenging as they will have to face a deadly six-headed monster and a fierce whirlpool before finally reaching port